An evaluation of the urbanization process of Galata (İstanbul) in the 19th century through the maps of Huber, d’Ostoya and Goad - Kunaci, Merve Ozbay; Gulersoy, Nuran Zeren (International Planning History Society Proceedings, 2018)
İstanbul underwent great changes to its urban texture as a result of the period of westernization that took place in the 19th Century. Beyoğlu and Galata, which represented the occidental and cosmopolitan face of the city, were among the settlements most influenced by these changes. This study aims to examine the spatial effects of these changes through the integration of old city maps of Beyoğlu and Galata with modern Geographic Information Systems (GIS). The maps of G. d'Ostoya (1858-1860), R. Huber (1887-1891) and Charles E. Goad (1904-1906) are the documents which are used in this context. The maps have been coordinated with GIS software and the items (such as buildings, roads, empty spaces) which they included as raster data have been transformed into vector data to make comparisons and superpositions possible within the GIS environment. Thus, the transformation of urban space can be revealed, and conclusions about how Galata was exposed to changes in the 19th Century can be drawn.